Elevated Serum Ferritin Levels in Gestational Diabetes Mellitus (GDM) at a Tertiary Care Hospital - Maria Jaan, Amna Saeed, Ayesha Munwar, Safia Yasmin, Nadia Zaman, Ayesh Zafar (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the frequency of elevated serum ferritin levels in gestational diabetes mellitus (GDM) at a tertiary care hospital. Material and methods: This cross sectional study was carried out from 10th July 2017 to 10th January 2018 at “Department of Obstetrics & Gynaecology, Shaikh Zayed Hospital, Rahim Yar Khan”. The sample included 114pregnant women with gestational diabetes mellitus both primi- and multi-gravida . Patients with known diabetics and hypertensives, patients with history of heart diseases and malignancies like breast cancer and brain tumor, severely anemic ladies were excluded.Routine investigations like FBS and serum ferritin levels were done. age, FBS, serum ferritin levels, gestational age, obesity, residential status and family history of GDM was recorded. Results: In present study, age range was 20-40 years and mean age of 30.535±4.29 years, mean gestational age 29.228±2.95 weeks, mean BMI 26.359±1.93 kg/m2, mean Baseline FBS 124.780±6.14 mg/dl and mean Serum ferritin level was 18.122±4.57 ng/ml. Majority of the patients (50.9%) belongs to 31-40 years age group. 33.3% patients were of obese category. 28.9% patients have family history of GDM. Patients from rural areas were 43% and from urban areas were 57%. Elevated serum ferritin level was seen in 102 (89.5%) patients. Conclusion: Serum ferritin level was high in GDM patients.We conclude that the elevated serum ferritin levelslead to gestational diabetes. Keywords: GDM, serum ferritin levels, obesity